(untitled) (Вісник: Міжнародні відносини, 2025)
Background. The growing influence of communication technologies and global events has reinforced the role of sports diplomacy as a foreign policy tool. Yet, scholars continue to classify it under cultural or public diplomacy. This ambiguity arises from the broad definition of soft power, in which both culture and sport serve as mechanisms of attraction and influence. The primary question is whether sports diplomacy functions as a complementary approach or as an independent instrument. Objectives. This study aims to define cultural and sports diplomacy boundaries, explain why the latter is underestimated, and highlight that institutionalization enables sports diplomacy to function as a standalone foreign policy tool. Methods. The research combines political, comparative, and content analyses with concretization. The methods help to explore the links to soft power, contrast environments, actors, and tools, and examine practical cases from France, Qatar, Saudi Arabia, and Australia. Results. The findings indicate that soft power provides a comprehensive framework for public, cultural, and sports diplomacy, with each operating in distinct settings. Cultural diplomacy operates in a symbolic–normative space shaped by the exchange of ideas and values, whereas sports diplomacy functions in a performance–competitive environment driven by organized events, sports networks, and mass audiences. Its late institutionalization and difficulty in measuring outcomes explain its marginalization. Nevertheless, the recent examples indicate change. The French model demonstrates how cultural diplomacy gained weight through institutionalization. A similar trend can be observed in sports diplomacy, where Qatar and Saudi Arabia utilize state-led events and tournaments to enhance their global reputation. Australia’s Sports Diplomacy 2030 strategy is a compelling example of how a country can use sports as a strategic diplomatic tool. Conclusions. Sports diplomacy can no longer be viewed as a subset of cultural diplomacy. The distinct environment, unique actors, and specific tools support its difference from other types of diplomacy. When backed by institutional frameworks, funding, and strategic vision, it emerges as an effective standalone foreign policy instrument. Recognizing its distinct role expands the diplomatic toolkit and offers states new ways to project soft power. Keywords: Sports diplomacy, cultural diplomacy, public diplomacy, soft power, foreign policy, culture, sports.